若M+(a^2-b^2)=(b-a)*N=2(a+2b)(a-b).求M,N的值。

2025-02-25 06:44:54
推荐回答(4个)
回答1:

M+(a^2-b^2)=2(a+2b)(a-b)
=2a^2+ab-2b^2
=a^2-b^2+a^2+ab-b^2
(b-a)*N=2(a+2b)(a-b)
N=2(a+2b)(a-b) /(b-a)
N=-2(a+2b)(b-a)/(b-a)
N=-2(a+2b)
N=-2a-4b

回答2:

m=0 n=-2a

回答3:

M+(a+b)(a-b)=(a-b)*(-N)=(2a+4b)(a-b)
=>N=-2a-4b M=(2a+4b-a-b)(a-b)=(a+3b)(a-b)=a^2-3b^2+2ab

回答4:

M+(a^2-b^2)=2(a+2b)(a-b)=(2a+4b)(a-b)
M+(a+b)(a-b)=(2a+4b)(a-b)=(a+3b)(a-b)+(a+b)(a-b)
M=(a+3b)(a-b)=a^2+2ab-3b^2

(b-a)*N=2(a+2b)(a-b)
(a-b)(-N)=2(a+2b)(a-b)
(-N)=2(a+2b)=2a+4b
N=-2a-4b